Coenzyme Q10 deficiency in mitochondrial DNA depletion syndromes - Montero, Raquel (2013)
We evaluated coenzyme Q10 (CoQ) levels in patients studied under suspicion of mitochondrial DNA depletion syndromes (MDS) (n = 39). CoQ levels were quantified by HPLC, and the percentage of mtDNA depletion by quantitative real-time PCR. A high percentage of MDS patients presented with CoQ deficiency as compared to other mitochondrial patients (Mann–Whitney-U test: p = 0.001). Our findings suggest that MDS are frequently associated with CoQ deficiency, as a possible secondary consequence of disease pathophysiology. Assessment of muscle CoQ status seems advisable in MDS patients since the possibility of CoQ supplementation may then be considered as a candidate therapy.